2014
DOI: 10.1666/13-147
|View full text |Cite
|
Sign up to set email alerts
|

The generaCalliotropisSeguenza andAmbercyclusn. gen. (Vetigastropoda, Eucyclidae) from the Early Jurassic of Argentina

Abstract: The systematic position of the fossil species referred toCalliotropisis currently under debate due to the striking resemblance between these forms with their extant counterparts in general shell morphology and ornament pattern. We propose two temporal subgenera ofCalliotropis:Calliotropis(Riselloidea) for Mesozoic species andCalliotropis(Calliotropis) for Cenozoic and Recent taxa. We also synonymize the families Eucyclidae and Calliotropidae, and redescribe the type genus of Eucylidae based on topotypic materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 29 publications
1
33
0
Order By: Relevance
“…Hokkaidoconchids range from the Late Jurassic to the EoceneOligocene (Gill et al, 2005;Kaim et al, 2014). The oldest known species is Hokkaidoconcha novacula from the Late Jurassic (Oxfordian) Beauvoisin hydrocarbon seep site (Kiel et al, 2010), with ‗Cerithium elatum' from Novaya Zemlya (this study) being coeval or slightly…”
Section: Relationships With Other Late Mesozoic Seep Faunasmentioning
confidence: 58%
See 2 more Smart Citations
“…Hokkaidoconchids range from the Late Jurassic to the EoceneOligocene (Gill et al, 2005;Kaim et al, 2014). The oldest known species is Hokkaidoconcha novacula from the Late Jurassic (Oxfordian) Beauvoisin hydrocarbon seep site (Kiel et al, 2010), with ‗Cerithium elatum' from Novaya Zemlya (this study) being coeval or slightly…”
Section: Relationships With Other Late Mesozoic Seep Faunasmentioning
confidence: 58%
“…For example, the chemosymbiotic protobranch bivalve genus Nucinella, which occur in Late Tithonian bituminous limestones, is known from some of water faunas and had broad palaeobiogeographic ranges (e.g. Oliver and Taylor, 2012;Ferrari et al, 2014). Interestingly, the Late Berriasian-Early Valanginian sandy limestones lack the seep-restricted dimerelloid brachiopod Peregrinella, which are very common in some Late…”
Section: Relationships With Other Late Mesozoic Seep Faunasmentioning
confidence: 99%
See 1 more Smart Citation
“…Preliminary biostratigraphic analyses carried out in the southern and west-central Chubut Province (Pagani et al, 2012;Ferrari, 2013Ferrari, , 2014a indicated a late Pliensbachian-early Toarcian age for these deposits. Moreover, Damborenea and Ferrari (2008), Ferrari (2009Ferrari ( , 2011aFerrari ( , b, 2012Ferrari ( , 2013Ferrari ( , 2014a, Ferrari et al (2014) and Pagani et al (2011Pagani et al ( , 2012 recently carried out new studies on the taxonomic composition of the faunas in the Early Jurassic of south-western and central Chubut Province, including the investigation of new fossil localities and the collection of Early Jurassic material.…”
Section: Introductionmentioning
confidence: 99%
“…Several Argentinean Early Jurassic marine gastropods have been described by Ferrari (2009Ferrari ( , 2011Ferrari ( , 2012Ferrari ( , 2013Ferrari ( , 2014aFerrari ( , 2014b and Ferrari et al (2014) from the Chubut Province. Up to date, 13 gastropod families from the Early Jurassic (late Pliensbachianearly Toarcian) marine deposits of the Mulanguiñeu and Osta Arena formations (Chubut Province), representing 20 genera, 2 subgenera and at least 30 species are reported.…”
Section: Introductionmentioning
confidence: 99%